Spatial-temporal evolution and multi-scenario prediction of carbon emissions from land use in the adjacent areas of nature reserves - Yuan Li; Yu-Ling Peng; Wei-Ying Cheng; Hao-Na Peng (Ecological Indicators)
The carbon emissions stemming from land use in adjacent areas exert a significant influence on the ecological balance of natural reserves. Examining carbon emission patterns linked to land use enables a deeper understanding of carbon dynamics in adjacent regions, thus safeguarding the functional integrity of natural reserves as vital carbon sink zones. This study focused on the protection and development belt of Wuyi Mountain National Park,11 For convenience of presentation, the protection and development belt of Wuyi Mountain National Park is abbreviated in the article as “the Belt”. a typical adjacent area of a nature reserve. Through the integration of spatial and statistical data, it examined the intensity and distribution characteristics of carbon emissions from 2000 to 2020. Additionally, the study employed the PLUS model to forecast land use trends and overall carbon emissions across various scenarios, including natural development, carbon sink enhancement, and carbon source control, for the years 2030 and 2060. Results indicated: (1) Between 2000 and 2020, the total carbon absorption capacity of the protection and development belt of Wuyi Mountain National Park showed a diminishing trend, contrasting with the rising trend in total carbon emissions; (2) In the vicinity of the natural reserve, there was discernible spatial variation in carbon emissions associated with land use. The eastern regions exhibited elevated emissions, whereas the southern regions demonstrated comparatively lower emissions. The extent of carbon sources continued to grow, with areas exhibiting low, medium, and high carbon emissions all displaying expansion tendencies. Areas with robust carbon absorption capacities consistently showed a decreasing trend; (3) Across all three scenarios, land allocated for construction emerged as the predominant source of carbon emissions. Notably, the carbon source control scenario exhibited the smallest net carbon emissions from land use, underscoring the significance of carbon reduction as the fundamental strategy for achieving carbon neutrality goals. This research can offer insightful experience for simulating land use patterns and estimating carbon emissions in adjacent areas with similar nature reserves, contributing to the proposal of targeted carbon neutrality policies and management measures, thereby facilitating the transition of nature reserves and their surrounding areas towards a low-carbon development path.